STRATEGI KOMUNIKASI UMKM DENGAN PELANGGAN DALAM MENINGKATKAN KEPERCAYAAN MEREK : KAJIAN LITERATUR - Rahma Saiyed; Ummu Kalsum; Akbar Said (Universitas Ichsan Sidenreng Rappang, 2025)
Brand trust is one of the factors that determine the sustainability of micro, small, and medium enterprises (MSMEs), especially in the business world which is currently increasingly competitive in presenting a variety of products. For MSME actors, brand trust is created as a result of the quality of two-way communication between MSME actors and their customers. This article focuses on analyzing the communication strategies used by MSME actors with customers in increasing brand trust through a literature review framework. The methodology uses a review of narrative literature from national and international journal articles published between 2020 and 2026, sourced from Google Scholar, SINTA, and Scopus databases. The findings show that two-way, interpersonal, transparent, and empathetic communication strategies play a crucial role in fostering brand trust. Besides that, the implementation of digital communication strategies through social media platforms has proven to be effective when done relationally compared to transactional approaches. A synthesis of literature explains that two-way communication and consistency of messages are fundamental factors in strengthening the relationship between MSMEs and their customers. This article describes the conceptual framework of MSME communication strategies and identifies related research gaps that require exploration in the advancement of communication management going forward.